A unique case of concurrent chronic lymphocytic leukemia/small lymphocytic lymphoma and lymphomatoid papulosis in the same biopsy. (3rd February 2015) - Hibler, J.; Salavaggione, Andrea L.; Martin, Ann; Gru, Alejandro A.
<x xml:space="preserve">Abstract</x> Chronic lymphocytic leukemia (CLL/SLL) is the most common leukemia in the western world and its cutaneous dissemination a very uncommon phenomenon. Lymphomatoid papulosis (LyP) is a CD30+ lymphoproliferative disorder characterized by chronic, recurrent and self healing skin lesions. Up to 20% of patients with LyP have a coexistent lymphoma. While the association between the two entities has been reported, their coexistence has never been documented. We describe a 74‐year‐old man with known CLL and thrombocytopenia who presented with a 2 year history of recurrent nodules and plaques to both arms and legs that resolved within 4–6 weeks after administration of rituximab and bendamustin for his CLL treatment. His biopsies showed an atypical lymphoid infiltrate, composed of large and pleomorphic cells with a nodular and interstitial pattern in a background of eosinophils. Immunohistochemical staining revealed a pattern of two separate yet coexisting neoplastic processes; a large CD30 positive T‐cell lymphoproliferative disorder, while the other one was diagnostic of a neoplastic B‐cell process (leukemia cutis). A diagnosis of coexistent LyP and cutaneous involvement by CLL/SLL was rendered. The simultaneous presence of both disorders can be a pitfall in the differential diagnosis of large cell lymphomas, such as Richter's transformation of CLL/SLL.